Exploratory Analysis of a GGSN’s PDP Context Signaling Load - Florian Metzger; Albert Rafetseder; Peter Romirer-Maierhofer; Kurt Tutschku (Journal of Computer Networks and Communications)
This paper takes an exploratory look on control plane signaling in a mobile cellular core network. In contrast to most contributions in this field, our focus does not lie on the wireless or user-oriented parts of the network, but on signaling in the core network. In an investigation of core network data we take a look at statistics related to GTP tunnels and their signaling. Based on the results thereof we propose a definition of load at the GGSN and create an initial load queuing model. We find signs of user devices putting burden on the core network through their behavior.